Effects of Adenotonsillectomy on Parent-Reported Behavior in Children With Obstructive Sleep Apnea - Thomas, Nina Hattiangadi (Sleep, 2017)
OBJECTIVES: The childhood obstructive sleep apnea syndrome (OSAS) is associated with behavioral abnormalities. Studies on the effects of OSAS treatment on behavior are conflicting, with few studies using a randomized design. Further, studies may be confounded by the inclusion of behavioral outcome measures directly related to sleep. The objective of this study was to determine the effect of adenotonsillectomy on behavior in children with OSAS. We hypothesized that surgery would improve behavioral ratings, even when sleep symptom items were excluded from the analysis. METHODS: This was a secondary analysis of Child Behavior Checklist (CBCL) data, with and without exclusion of sleep-specific items, from the Childhood Adenotonsillectomy Trial (CHAT). CBCL was completed by caregivers of 380 children (7.0+1.4 [range 5–9] years) with OSAS randomized to early adenotonsillectomy (eAT) versus 7 months of watchful waiting with supportive care (WWSC). RESULTS: There was a high prevalence of behavioral problems at baseline; 16.6% of children had a Total Problems score in the clinically abnormal range. At follow-up, there were significant improvements in Total Problems (p < .001), Internalizing Behaviors (p = .04), Somatic Complaints (p = .01), and Thought Problems (p = .01) in eAT vs. WWSC participants. When specific sleep-related question items were removed from the analysis, eAT showed an overall improvement in Total (p = .02) and Other (p = .01) problems. Black children had less improvement in behavior following eAT than white children, but this difference attenuated when sleep-related items were excluded. CONCLUSIONS: This large, randomized trial showed that adenotonsillectomy for OSAS improved parent-rated behavioral problems, even when sleep-specific behavioral issues were excluded from the analysis.